CONFRONTING THE BIOFUEL-CARBON EMISSIONS-BIODIVERSITY TRILEMMA IN A PANEL OF BIOFUEL CONSUMING COUNTRIES - Zaman, Khalid (Malaysian Journal of Science, 2016)
Since our growth, the human-made activities for better living damage the global environment. Biodiversity is no exception that damages due to massive humanization process. This study focused on the relationship between biofuels consumption, carbon dioxide emissions and biodiversity in a panel of 12 selected biofuels consuming countries for a period of 2000-2013. The study employed panel fixed effect and panel random effect model to obtain the parameter estimates. The results found that biofuels consumption and carbon dioxide emissions both damage the biodiversity in a panel of countries. The results confirm the cointegration relationship between the variables. The quest for the renewable energy fuels for human development remains the keen agenda for the policy makers, however, the war for better health and wealth always exhausts the natural environment of the world’s precious natural resources that should be taken into account in the next call for alerts. Keywords: Biofuels consumption; Biodiversity; Carbon dioxide emissions; Panel Fixed Effect; Panel Random Effect; Panel cointegration.